Analysis of Needs in the Development of Assessment of Autistic Children Through Art Therapy at Inclusive Early Childhood Education in Surakarta City - Sixta Madubala; Nur Fajrie; Sri Utaminingsih (STKIP Taman Siswa Bima, 2023)
The assessment of autistic children in inclusive PAUD has not been optimal, while the assessment through an art therapy approach has not been carried out, so a needs analysis is needed. Assessment is a learning process to measure the achievement of children's development, the purpose of this study was to analyze aspects supporting the needs of developing an assessment model for autistic children through an art therapy approach. The research method used is a mix-methods approach with a sequential explanatory variant. Data using questionnaire analysis is strengthened by in-depth interviews, observation and document study. The research sample used 13 teachers of 13 children at Inclusion PAUD in Surakarta City with autism. The results obtained were that teachers had carried out assessments of autistic children in their institutions, the results of assessing the ability of students in good grades only reached a maximum of 15%, quite good results on the quality of children's work by 68%. The concentration ability of children to achieve good results is only 9%, the remaining 54% are still in an adequate position, there are even those who are very lacking, there are 15%, the remaining 38% have poor concentration abilities. The results of the teacher's interviews and observations state that the assessment so far has not been optimal, the children are not focused, the approach applied is not attractive, the teacher has not used the art therapy approach. Based on the research results, it is necessary to develop an assessment model for autistic children through an art therapy approach, namely applying two-dimensional art therapy in the assessment process for autistic children.